La nouvelle justice naturelle : l'administrateur « équitable et raisonnable » - Brown, L. (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
This paper, based on a public lecture given in October, 1979, at the Faculty of Law of Laval University, gives an account of recent developments in English administrative law concerning the concepts of fairness and reasonableness. Tracing back the origins of the concept of fairness and its revival in Ridge v. Baldwin, the paper illustrates its current use by discussing several recent cases where Lord Denning's thinking appears to have had a strong influence. The contents of the administrator's duty to act fairly is described by the metaphor of a sliding scale allowing for a great diversity of requirements to suit the variety of statutory contexts. As to the concept of reasonableness, the paper brings out its close affinities with private law, and its progressive introduction as a standard by which courts rule on the legality of administrative decisions. This process has recently culminated in the Tameside and Laker cases, which are discussed at length. Both fairness and reasonableness may be shown to have rough equivalents in other European legal systems. The recent case of R. v. Barnsley Borough Council, ex p. Hook may point to another ground for cross-influences between English, French and German administrative law, especially in the context of EEC law : a concept of « proportionality » may be emerging in England — a distant outgrowth of the prohibition against « excessive fines » and « cruel and unusual punishment » in the Bill of Rights.